The effect of auditory-motor mapping training in Korean on the speech output of children with autism - Kim, Hae Sun, author; Davis, William B., advisor; LaGasse, A. Blythe, advisor; Fails, Anna Dee, committee member (Colorado State University. Libraries, 2014)
Given the lower verbal output in many children with autism spectrum disorders (ASD), a number of interventions in English are available for them. However, currently there are no interventions specifically researched with children with ASD who come from different language backgrounds other than English. The present study examined the effect of an intonation-based treatment called auditory-motor mapping training (AMMT) to facilitate verbal output in two children with a diagnosis of ASD from Korean-speaking households. Both participated in a total of nine AMMT sessions in addition to four assessments over a 4-week period. A baseline assessment was conducted prior to the first treatment, and probe assessments were conducted after treatment session 3, 6, and 9. Each child's verbal production including consonants and vowels were measured. The results showed some improvements in the production of consonants and vowels over the treatment period; however, the differences were not significant. Although no statistically significant results were observed in this pilot study, more conclusive results may be observed in future studies adhering to the suggested recommendations.
Keywords: auditory-motor mapping training; auditory motor mapping training; autism; autism spectrum disorder; melodic intonation therapy; music therapy